2014
DOI: 10.1007/s00024-014-0985-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cavities Using the GPR, LIDAR and GNSS Techniques

Abstract: The study of the many types of natural and manmade cavities in different parts of the world is important to the fields of geology, geophysics, engineering, architectures, agriculture, heritages and landscape. Ground-penetrating radar (GPR) is a noninvasive geodetection and geolocation technique suitable for accurately determining buried structures. This technique requires knowing the propagation velocity of electromagnetic waves (EM velocity) in the medium. We propose a method for calibrating the EM velocity u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We performed a two-dimensional (2D) Kirchhoff migration before and after SVD using a constant ground velocity (0.16 m/ns calculated from diffraction hyperbola fitting). It has been shown that TLS can be utilized to determine a best fit ground velocity [24]. However, that is only possible when TLS data have captured subsurface structures (e.g., a cave or tunnel).…”
Section: Migration Of Svd-filtered Gpr Datamentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a two-dimensional (2D) Kirchhoff migration before and after SVD using a constant ground velocity (0.16 m/ns calculated from diffraction hyperbola fitting). It has been shown that TLS can be utilized to determine a best fit ground velocity [24]. However, that is only possible when TLS data have captured subsurface structures (e.g., a cave or tunnel).…”
Section: Migration Of Svd-filtered Gpr Datamentioning
confidence: 99%
“…Global Positioning Systems (GPS) can be paired with GPR equipment to synchronously collect geospatial and geophysical data. It has been shown that high-precision height information is valuable in archaeological settings e.g., [21][22][23][24][25]. Digital elevation models (DEM) derived from airborne laser scanning (ALS) datasets can provide full coverage of a survey area (ALS is also referred to as airborne Light Detection and Ranging or airborne LiDAR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation